Investigation on Electrospun and Solvent-Casted PCL-PLGA Blends Scaffolds Embedded with Induced Pluripotent Stem Cells for Tissue Engineering - Mariella Rosalia; Martina Giacomini; Erika Maria Tottoli; Rossella Dorati; Giovanna Bruni; Ida Genta; Enrica Chiesa; Silvia Pisani; Maurilio Sampaolesi; Bice Conti (MDPI AG, 2023)
The design, production, and characterisation of tissue-engineered scaffolds made of polylactic-co-glycolic acid (PLGA), polycaprolactone (PCL) and their blends obtained through electrospinning (ES) or solvent casting/particulate leaching (SC) manufacturing techniques are presented here. The polymer blend composition was chosen to always obtain a prevalence of one of the two polymers, in order to investigate the contribution of the less concentrated polymer on the scaffolds' properties. Physical-chemical characterization of ES scaffolds demonstrated that tailoring of fibre diameter and Young modulus (YM) was possible by controlling PCL concentration in PLGA-based blends, increasing the fibre diameter from 0.6 to 1.0 µm and reducing the YM from about 22 to 9 MPa. SC scaffolds showed a "bubble-like" topography, caused by the porogen spherical particles, which is responsible for decreasing the contact angles from about 110° in ES scaffolds to about 74° in SC specimens. Nevertheless, due to phase separation within the blend, solvent-casted samples displayed less reproducible properties. Furthermore, ES samples were characterised by 10-fold higher water uptake than SC scaffolds. The scaffolds suitability as iPSCs culturing support was evaluated using XTT assay, and pluripotency and integrin gene expression were investigated using RT-PCR and RT-qPCR. Thanks to their higher wettability and appropriate YM, SC scaffolds seemed to be superior in ensuring high cell viability over 5 days, whereas the ability to maintain iPSCs pluripotency status was found to be similar for ES and SC scaffolds.